2004
DOI: 10.1016/j.ica.2004.06.061
|View full text |Cite
|
Sign up to set email alerts
|

Control mechanisms for transport and nonlinear optical response in organic materials: a tale of twists and barriers

Abstract: Simple electronic structure models are used to address two significant challenges in organic materials chemistry, the design of chromophores for strong electro-optic response (and low-energy optical absorption), and the prediction of relative mobilities and charge injection barriers for conductive oligomers. For electro-optic response, we examine two chromophore classes where twisting around an interring bond can tune the electronic structure from aromatic (zwitterionic) to quinoid (neutral). The calculated no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 66 publications
(41 reference statements)
0
9
0
Order By: Relevance
“…As stated earlier, this presents the opportunity to directly compare the results from these computational studies (with no free parameters) with experimentally obtained results to directly validate the variable-range hopping model. The use of first principles quantum chemistry, in particular, density functional theory, to calculate the parameters of k et and use them to explain experimental charge transport results has been demonstrated in the literature …”
Section: Methodsmentioning
confidence: 99%
“…As stated earlier, this presents the opportunity to directly compare the results from these computational studies (with no free parameters) with experimentally obtained results to directly validate the variable-range hopping model. The use of first principles quantum chemistry, in particular, density functional theory, to calculate the parameters of k et and use them to explain experimental charge transport results has been demonstrated in the literature …”
Section: Methodsmentioning
confidence: 99%
“…Previous work has shown that materials with large (hyper)polarizabilities generally exhibit significantly higher dielectric responses than other molecular materials. 21,39,40 In this regard, electron-donating and electron-accepting moieties are known to enhance molecular (hyper)polarizabilities when introduced in tandem to conjugated π-systems. 41−44 These molecular materials, commonly referred to as DBA materials ( Figure 1) have inspired significant research in the scientific community for implementation in nonlinear optics, 44−47 charge transfer, 48−50 and charge transport.…”
Section: ■ Introductionmentioning
confidence: 99%
“…8,[48][49][50] In other cases, such as twisted chromophores the situation is more complex. 49,51,52 The important observation is that further improvements of molecular first hyperpolarizability can be expected and the realization of electro-optic activity on the order of 1000 pm/V is likely an achievable goal.…”
Section: Optimizing Chromophore Molecular First Hyperpolarizability βmentioning
confidence: 99%